PENINGKATAN HASIL BELAJAR PENJUMLAHAN DAN PENGURANGAN MENGGUNAKAN MODEL GAME BASED LEARNING BERBANTUAN ULAR TANGGA DI KELAS II SDN 12 PADANG BESI KOTA PADANG - Prima Dola, Melsi; Suciana, Fadila; Ningsih, Yarisda; Desyandri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Low mathematics performance among second-grade students at SDN 12 Padang Besi, Padang City especially in the topic of addition and subtraction served as the primary motivation for this research. Several contributing factors were observed, namely minimal use of varied and innovative teaching approaches, suboptimal utilization of instructional media, weak student focus and participation during lessons, and shallow grasp of basic arithmetic principles among learners. To address these issues, the researcher set out to investigate whether applying a Game Based Learning (GBL) approach, supported by Snake and Ladder media, could raise students' academic performance. A Classroom Action Research (CAR) framework combining qualitative and quantitative methods was employed, unfolding across two cycles that each followed four stages: planning, implementation, observation, and reflection. Both testing and non-testing instruments were used to collect data, drawing on a research sample composed of one second-grade classroom teacher along with 21 pupils from the same grade at SDN 12 Padang Besi. Results pointed to steady gains across all measured dimensions. Teaching module quality rose from 87.45% (categorized as Good) during the first cycle to 95.8% (Very Good) in the second. Similarly, teacher performance climbed from 85.13% to 95.3%, moving from the Good to Very Good category, and student activity levels followed the same pattern, increasing from 85.13% to 95.3%. Meanwhile, students' mean achievement scores rose from 79.75 in Cycle I to 86.9 in Cycle II. Taken together, these outcomes confirm that Game Based Learning combined with Snake and Ladder media serves as an effective strategy for boosting students' understanding and results in addition and subtraction.